2022
DOI: 10.1108/k-04-2021-0294
|View full text |Cite
|
Sign up to set email alerts
|

Does social media usage boost career prospects of women: an exploratory study in the academia

Abstract: PurposeThis paper draws on the affordance perspective, to explore the social media (SM) usage experiences that might render valuable for academic women professionals, for knowledge exchange, networking and success. Owing to the increased SM usage during COVID-19 pandemic, this paper tries to find out that in what ways do SM affordances facilitate the underprivileged group of women professionals to grow in their careers in a masculine, conservative society through knowledge exchange.Design/methodology/approachB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 114 publications
(230 reference statements)
0
5
0
Order By: Relevance
“…Earlier researchers (e.g. Sarwar and Imran, 2019; Sarwar et al ., 2022a, b) have shown that career-related outlooks, attitudes and behavior of Pakistani women within contemporary organizations vary as compared to men. Therefore, scholars have used such covariates (Sarwar et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier researchers (e.g. Sarwar and Imran, 2019; Sarwar et al ., 2022a, b) have shown that career-related outlooks, attitudes and behavior of Pakistani women within contemporary organizations vary as compared to men. Therefore, scholars have used such covariates (Sarwar et al.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier research has also shown that when personnel perceive to be socially disconnected and isolated, it increases their depression (Li and Huynh, 2020). Similarly, a recent study (Sarwar et al ., 2022a, b) showed that the fear of a pandemic leads to emotional exhaustion in employees, which in turn negatively affects their performance. Therefore, it would be interesting to study how during the days of a pandemic, how ostracized employees would react to depletion in their resource reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…During a pandemic, leadership and management need to emphasize the importance of staying in touch with work peers (remotely) for assistance and to create facilitating relationships at the workplace (Toker et al ., 2015). Managers may highlight the role of social media usage during such times (Sarwar et al. , 2022c).…”
Section: Discussionmentioning
confidence: 99%
“…It might be beneficial to engage employees in relaxing activities like social media usage (Sarwar et al. , 2022b) and exercise that may help them in reducing the fear of COVID-19 and emotional exhaustion leading to work-life conflict (Sonnentag et al.…”
Section: Discussionmentioning
confidence: 99%
“…It might be beneficial to engage employees in relaxing activities like social media usage (Sarwar et al, 2022b) and exercise that may help them in reducing the fear of COVID-19 and emotional exhaustion leading to work-life conflict (Sonnentag et al, 2010). Despite adopting such measures, since outbreaks of contagious diseases cannot be ruled out, therefore its negative effects on employees' performance and family life cannot be avoided.…”
Section: Practical Implicationsmentioning
confidence: 99%